Caracterização dos genomas do tatu-peba e tatu-canastra e genômica comparativa na superordem Xenarthra - Inforzato, Alexandre Romero (Universidade Federal de São Carlos, 2024)
This study investigated the genetic diversity and genes under positive selection in xenarthrans using genomes and sequencing data currently available in the public database GenBank (NCBI), focusing on Euphractus sexcinctus (six-banded armadillo) and Priodontes maximus (giant armadillo), whose genome assemblies were produced by the author. For comparative genomics analyses, the novel assemblies of E. sexcinctus and P. maximus were added to the nine existing xenarthran genomes in the GenBank database (Bradypus variegatus, Cabassous unicinctus, Chaetophractus vellerosus, Choloepus didactylus, Choloepus hoffmanni, Dasypus novemcinctus, Myrmecophaga tridactyla, Tamandua tetradactyla, and Tolypeutes matacus), increasing the genomic representation of a clade with only 31 living species and a rich evolutionary history. The genomic characterization revealed challenges in genome assembly, especially for P. maximus, whose low coverage and high fragmentation limited gene content completeness and, consequently, the prediction of expressed proteins. To mitigate this effect, the RagTag v2.1.0 tool was used to reduce fragmentation in several of the assemblies, significantly increasing the prediction of expressed proteins and orthologous genes. For selection analysis, expressed proteins were predicted using the GeMoMa v1.9 tool, single-copy orthologous genes were identified using OrthoFinder v2.5.5, multiple codon alignments were performed with PRANK v.170427, phylogenetic trees were constructed with IQ-Tree2 v2.1.2, and positive selection analysis was conducted with HyPhy v2.5.8, using the BUSTED function. Candidate genes identified as being under positive selection were validated with Xia's substitution saturation test in the DAMBE v7.3.32 software and functionally annotated with the emapper v2.1.12 tool from the eggNOG v5.0.2 package. This led to the identification of 15 genes under positive selection, including keratin (KRT10), which may have conferred evolutionary advantages to xenarthrans. The autosomal heterozygosity analysis showed significant variations among the species. The giant anteater (Myrmecophaga tridactyla) and the giant armadillo (Priodontes maximus), classified as "Vulnerable" by the IUCN, exhibited low heterozygosity, indicating reduced genetic diversity. In contrast, the southern three-banded armadillo (Tolypeutes matacus), although classified as "Near Threatened", displayed high heterozygosity, and the Linnaeus's two-toed sloth (Choloepus didactylus) and Hoffmann's two-toed sloth (Choloepus hoffmanni) – despite being both classified as “Least Concern” – exhibited reduced heterozygosity. The analyses provided detailed data on the genetic diversity and evolution of xenarthrans, contributing to the understanding of these species and their conservation needs.
Characterization of the genomes of the six-banded armadillo and giant armadillo and comparative genomics in the superorder Xenarthra
Keywords: Xenarthra; Tatu; Armadillo; Genoma; Genome; Filogenômica; Phylogenomics; Análise de seleção; Selection analysis; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL